The biology of ovarian cancer of epithelial origin - Rabinerson, D; Kaplan, B; Levavi, H; Neri, A (Israel journal of medical sciences, 1996)
Ovarian cancer of epithelial origin is associated with the highest mortality rate of all gynecologic malignancies. Since no symptoms or signs are manifested at the early stages of the disease, it is no surprise that in 75% of patients peritoneal metastases are found during primary surgery. Despite advances in conservative treatment methods (invasive and noninvasive), screening for early detection of the disease is not yet available, and the overall survival rate is as low as 5-15%. Recent studies in molecular biology have drawn attention to different research directions in ovarian cancer and have contributed much to our understanding of this disease and its underlying pathologic mechanisms. This review is intended to highlight some of the new aspects of this research, specifically: hereditary ovarian cancer, genetic background in terms of chromosomal changes, DNA anomalies, oncogenes, tumor-suppressor genes, peptide growth factors and cytokines, invasiveness and metastasis, and finally, drug resistance. No breakthrough has as yet occurred in any of the subjects screened in this review, but results are promising. The clinical application of the steadily increasing knowledge in the biology of ovarian cancer may assist in the development of new treatment modalities that will improve survival.